Pembrolizumab Plus Ipilimumab or Placebo for Metastatic Non-Small-Cell Lung Cancer With PD-L1 Tumor Proportion Score >= 50%: Randomized, Double-Blind Phase III KEYNOTE-598 Study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
PURPOSE Pembrolizumab monotherapy is standard first-line therapy for metastatic non-small-cell lung cancer (NSCLC) with programmed death ligand 1 (PD-L1) tumor proportion score (TPS) >= 50% without actionable driver mutations. It is not known whether adding ipilimumab to pembrolizumab improves efficacy over pembrolizumab alone in this population. METHODS In the randomized, double-blind, phase III KEYNOTE-598 trial (ClinicalTrials.gov identifier: ), eligible patients with previously untreated metastatic NSCLC with PD-L1 TPS >= 50% and no sensitizing EGFR or ALK aberrations were randomly allocated 1:1 to ipilimumab 1 mg/kg or placebo every 6 weeks for up to 18 doses; all participants received pembrolizumab 200 mg every 3 weeks for up to 35 doses. Primary end points were overall survival and progression-free survival. RESULTS Of the 568 participants, 284 were randomly allocated to each group. Median overall survival was 21.4 months for pembrolizumab-ipilimumab versus 21.9 months for pembrolizumab-placebo (hazard ratio, 1.08; 95% CI, 0.85 to 1.37; P = .74). Median progression-free survival was 8.2 months for pembrolizumab-ipilimumab versus 8.4 months for pembrolizumab-placebo (hazard ratio, 1.06; 95% CI, 0.86 to 1.30; P = .72). Grade 3-5 adverse events occurred in 62.4% of pembrolizumab-ipilimumab recipients versus 50.2% of pembrolizumab-placebo recipients and led to death in 13.1% versus 7.5%. The external data and safety monitoring committee recommended that the study be stopped for futility and that participants discontinue ipilimumab and placebo. CONCLUSION Adding ipilimumab to pembrolizumab does not improve efficacy and is associated with greater toxicity than pembrolizumab monotherapy as first-line treatment for metastatic NSCLC with PD-L1 TPS >= 50% and no targetable EGFR or ALK aberrations. These data do not support use of pembrolizumab-ipilimumab in place of pembrolizumab monotherapy in this population. (C) 2021 by American Society of Clinical Oncology
Keywords: COMBINED NIVOLUMAB; RESPONSE CRITERIA; CHEMOTHERAPY; SURVIVAL